Green Berets in the Vanguard Inside Special Forces, 1953-1963. - Archer Jr., Chalmers (Naval Institute Press, 2018)
The author of an award-winning memoir about growing up black in Mississippi, Chalmers Archer turns his attention in this book to his experiences as one of the first members of the U.S. Army's Special Forces.